South Florida Gardening Calendar - Sydney Park Brown (EDIS)
Prune non-spring flowering shrubs and trees in January to improve form. In March, plant warm-season vegetables, such as sweet corn, cucumber, watermelon, and pepper, for late spring harvest. If bahiagrass lawns are yellowing in May, iron may correct the problem. Butterfly lily and gladiolus are bulbs that can be planted during the middle of summer. Plant gladiolus every 2 weeks in September to stagger blooming. This 11-page fact sheet tells what to plant and what to do in your south Florida garden, year-round. Written by Sydney Park Brown and published by the UF Department of Environmental Horticulture, April 2012.